Pengembangan Media Fun Thinkers Book Pada Tema 7 Subtema 1 Kelas V SDN 091453 Marihat Raja Kecamatan Dolok Panribuan T.A 2022/2023 - Sonia Pangaribuan; Laurensia Masri Perangin-Angi (Departement of Mathematics Education, 2023)
This reaearch purpose to determine the feasibility, practicality and effectiveness of using Fun Thinkers Book media in learning theme 7 sub-theme 1 learning 1 for class V at SDN 091453 Marihat Raja. This type of research is R&D (Research and Development) development research using the ADDIE model through 5 stages, namely the Analysis, Design, Development, Implementation and Evaluation stages. The subjects of this study were all fifth grade students at SDN 091453 Marihat Raja with a total of 13 students. Data collection techniques using interviews, questionnaires/questionnaires, tests and documentation. The feasibility test was aimed at FIP ​​PGSD UNIMED lecturers, the practical test was aimed at fifth grade teachers at SDN 091453 Marihat Raja and the effectiveness test was aimed at fifth grade students at SDN 091453 Marihat Raja. The results of the developed media research show: 1) Fun Thinkers Book learning media in learning theme 7 sub-theme 1 learning 1 is stated to be very valid with a score of 92% for material questionnaire experts, 86% questionnaire experts for media, 88% questionnaire experts for test instruments, 92 % questionnaire experts for education practitioners, 86% material experts, 82% media experts in stage I and 86% media experts in stage II and 92% test instrument experts. 2) The teacher's assessment of class V SDB 091453 Marihat Raja was stated to be very practical to apply with a score of 91%, 3) The student's response to doing the pretest and post-test during field trials using the Fun Thi